Harmonizing the Assessment of the Impacts of Natural Disasters to Florida Agriculture - Christa Dean Court; Alan W Hodges; Matthew Lollar (EDIS, 2020)
UF/IFAS Extension has developed an online survey instrument to improve collection of data on losses to Florida agricultural businesses following disasters and to assist agricultural stakeholders in times of disaster. Florida’s agricultural sector frequently experiences substantial adverse impacts during and after natural disasters. Depending on the size and scope of the disaster, agricultural business owners and employees could suffer reduced earnings, financial insecurity, and social stress, and consumers could experience temporary food insecurity. Timely provision of credible estimates of agricultural losses after a disaster is critical to an official disaster declaration and to timely provision of disaster relief and recovery, but collecting data on agricultural losses can present challenges. This 15-page fact sheet written by Christa Court, Alan Hodges, and Matt Lollar and published by the UF/IFAS Food and Resource Economics Department describes the online survey instrument, explains how to use it, and communicates how the data collected will be used in analyses of economic losses. https://edis.ifas.ufl.edu/fe1075